Variations in macrophage migration inhibitory factor gene are not associated with visceral leishmaniasis in India. Issue 3 (May 2019) - Mishra, Anshuman; Sundaravadivel, Pandarisamy; Tripathi, Sunil Kumar; Jha, Rajan Kumar; Badrukhiya, Jaydeep; Basak, Nipa; Anerao, Isha; Sharma, Akshay; Idowu, Ajayi Ebenezer; Mishra, Abhishek; Pandey, Sonika; Kumar, Umesh; et al.
Abstract: Background: The host genetic factors play important role in determining the outcome of visceral leishmaniasis (VL). Macrophage migration inhibitory factor (MIF) is an important host cytokine, which is a key regulator of innate immune system. Genetic variants in MIF gene have been found to be associated with several inflammatory and infectious diseases. Role of MIF is well documented in leishmaniasis diseases, including Indian visceral leishmaniasis, where elevated level of serum MIF has been associated with VL phenotypes. However, there was no genetic study to correlate MIF variants in VL, therefore, we aimed to study the possible association of three reported MIF gene variants −794 CATT, −173G > C and non-coding RNA gene LOC284889 in Indian VL phenotype. Methods: Study subjects comprised of 214 VL patients along with ethnically and demographically matched 220 controls from VL endemic regions of Bihar state in India. Results: We found no significant difference between cases and controls in allelic, genotypic and haplotype frequency of the markers analysed [-794 CATT repeats (χ2 = 0.86; p = 0.35; OR = 0.85; 95% CI = 0.61–1.19); −173 G > C polymorphism (χ2 = 1.11; p = 0.29; OR = 0.83; 95% CI = 0.59–1.16); and LOC284889 (χ2 = 0.78; p = 0.37; OR = 0.86; 95% CI = 0.61–1.20)]. Conclusion: Since we did not find any significant differences between case and control groups, we conclude that sequencing of complete MIF gene and extensive study on innate and adaptive immunity genes may help in identifying genetic variations that are associated with VL susceptibility/resistance among Indians.